Vertical average irradiance shapes the spatial pattern of winter chlorophyll-a in the Yellow Sea. (31st August 2019) - Lin, Lei; Wang, Yueqi; Liu, Dongyan
Abstract: Strong turbulence in temperate shelves during winter months enhances the vertical mixing of the water column, consequently pumps up nutrients and induces high turbidity in the upper ocean. Thus, light availability often becomes an important factor to impact phytoplankton biomasses and their spatial patterns in winter. To quantitatively assess the effect of light availability on the spatial pattern of phytoplankton in the Yellow Sea in winter, we used vertical average irradiance ( I m ) as a light index which denotes the average irradiance received by phytoplankton during their vertical motion, and then analyzed the spatial correlation between winter climatological I m and chlorophyll-a (Chl-a). The result from a set of high-resolution satellite-derived climatological data (2003–2016) demonstrated that there is a significantly positive correlation ( R = 0.71, p < 0.0001) between Chl-a and I m in space. The observational data of 2016 winter further showed that I m is much more important in determining the spatial pattern of Chl-a concentrations than nutrients, due to the availability of sufficient nutrients but very limited light availability for almost the entire sea area. Relatively high Chl-a regions (>1 mg/m 3 ) are in response to an environmental condition of I m > 50 μmol photons/m 2 /s, total suspended matter concentration (TSM) < 10 mg/L, and mixed layer depth (MLD) < 40 m. In coastal waters, TSM is the key factor to cause low I m ; while MLD is more important in deep offshore waters to determine the I m values. Highlights: 1. Strong spatial correlation between winter Chl-a and I m exists in the Yellow Sea. 2. PCA analysis on field observed data confirms the dominating role of I m in Chl-a. 3. Winter sufficient nutrients but limited light lead to the critical role of I m .